Kynurenic Acid Acts as a Signaling Molecule Regulating Energy Expenditure and Is Closely Associated With Metabolic Diseases - Zhen, Delong; Liu, Junjun; Zhang, Xu Dong; Song, Zehua (Frontiers in Endocrinology, 2022)
Kynurenic acid (KYNA) is an important bio-active product of tryptophan metabolism. In addition to its well-known neuroprotective effects on mental health disorders, it has been proposed as a bio-marker for such metabolic diseases as atherosclerosis and diabetes. Emerging evidence suggests that KYNA acts as a signaling molecule controlling the networks involved in the balance of energy store and expenditure through GPR35 and AMPK signaling pathway. KYNA plays an important role in the pathogenesis and development of several endocrine and metabolic diseases. Exercise training promotes KYNA production in skeletal muscles and increases thermogenesis in the long term and limits weight gain, insulin resistance and inflammation. Additionally, KYNA is also present in breast milk and may act as an anti-obesity agent in infants. Although we are far from fully understanding the role of KYNA in our body, administration of KYNA, enzyme inhibitors or metabolites may serve as a potential therapeutic strategy for treating metabolic diseases. The present review provides a perspective on the current knowledge regarding the biological effects of KYNA in metabolic diseases and perinatal nutrition.